Regulation of autophagy, mitochondrial dynamics, and cellular bioenergetics by 4-hydroxynonenal in primary neurons. Issue 11 (2nd November 2017) - Dodson, Matthew; Wani, Willayat Y.; Redmann, Matthew; Benavides, Gloria A.; Johnson, Michelle S.; Ouyang, Xiaosen; Cofield, Stacey S.; Mitra, Kasturi; Darley-Usmar, Victor; Zhang, Jianhua
ABSTRACT: The production of reactive species contributes to the age-dependent accumulation of dysfunctional mitochondria and protein aggregates, all of which are associated with neurodegeneration. A putative mediator of these effects is the lipid peroxidation product 4-hydroxynonenal (4-HNE), which has been shown to inhibit mitochondrial function, and accumulate in the postmortem brains of patients with neurodegenerative diseases. This deterioration in mitochondrial quality could be due to direct effects on mitochondrial proteins, or through perturbation of the macroautophagy/autophagy pathway, which plays an essential role in removing damaged mitochondria. Here, we use a click chemistry-based approach to demonstrate that alkyne-4-HNE can adduct to specific mitochondrial and autophagy-related proteins. Furthermore, we found that at lower concentrations (5–10 μM), 4-HNE activates autophagy, whereas at higher concentrations (15 μM), autophagic flux is inhibited, correlating with the modification of key autophagy proteins at higher concentrations of alkyne-4-HNE. Increasing concentrations of 4-HNE also cause mitochondrial dysfunction by targeting complex V (the ATP synthase) in the electron transport chain, and induce significant changes in mitochondrial fission and fusion protein levels, which results in alterations to mitochondrial network length. Finally, inhibition of autophagy initiation using 3-methyladenine (3MA) also results in a significant decrease in mitochondrial function and network length. These data show that both the mitochondria and autophagy are critical targets of 4-HNE, and that the proteins targeted by 4-HNE may change based on its concentration, persistently driving cellular dysfunction.